COMPARISON AMONG DIFFERENT DIAGNOSTIC METHODS IN THE STUDY OF TYPE AND ACTIVITY OF CHOROIDAL NEOVASCULAR MEMBRANES IN AGE-RELATED MACULAR DEGENERATION. Issue 2 (February 2019) - Ravera, Vittoria; Giani, Andrea; Pellegrini, Marco; Oldani, Marta; Invernizzi, Alessandro; Carini, Elisa; Cigada, Mario; Bottoni, Ferdinando; Staurenghi, Giovanni
Abstract : Purpose: To determine interobserver and intraobserver agreement in classifying the subtypes of choroidal neovascularization (CNV) and the decision of retreatment in patients affected by exudative age-related macular degeneration. Different imaging techniques were evaluated individually and compared with multiimaging. Methods: Fifty-two patients with naive CNV in age-related macular degeneration were evaluated after 3 monthly intravitreal injections of ranibizumab. Choroidal neovascularization subtype and activity were evaluated using spectral domain optical coherence tomography, infrared light, fundus autofluorescence, fluorescein angiography (FA), and indocyanine green angiography (ICGA). The evaluation was performed independently by 10 different retina specialists, 2 for each test. Other two operators analyzed all the information available together. Results: The interobserver k regarding the types of CNV was 0.69 for multiimaging, 0.63 for spectral domain optical coherence tomography, 0.43 for FA, and 0.46 for ICGA. The k values for interobserver for retreatment decision were 0.77 for multiimaging, 0.88 for spectral domain optical coherence tomography, 0.61 for infrared, 0.37 for fundus autofluorescence, 0.25 for FA, and 0.23 for ICGA. Fluorescein angiography, spectral domain optical coherence tomography, ICGA, and infrared showed good association with multiimaging on defining CNV activity ( P = 0.0003, P < 0.0001, P = 0.01, and P = 0.05, respectively). Conclusion: Optical coherence tomography and infrared evaluations of CNV activity were reproducible and strongly associated with multiimaging, whereas FA and ICGA evaluations showed poor reproducibility. Abstract : The authors evaluated different imaging modalities in the assessment of choroidal neovascularization types and activity. They found that spectral domain optical coherence tomography and infrared imaging are the most reproducible, with a strong correlation with multiimaging evaluation.